Hot work tool steel with excellent thermal conductivity

JP7629269B2Active Publication Date: 2025-02-13SANYO SPECIAL STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2019133602
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-07-19
Publication Date
2025-02-13
Estimated Expiration
2039-07-19

AI Technical Summary

Technical Problem

Existing hot work tool steels face challenges in achieving high thermal conductivity, hardness, softening resistance, and toughness due to imbalances in alloy composition and microstructure, leading to issues like wear, cracks, and reduced cooling efficiency in die casting and hot stamping molds.

Method used

A hot work tool steel with a specific alloy composition and microstructure, including C: 0.35-0.70%, Si: 0.01-1.20%, Mn: 0.01-1.50%, Cr: 0.30-4.00%, Cu: 0.05-3.50%, Mo: 0.00-3.00%, W: 0.00-6.00%, V: 0.10-0.55%, B: 0.0001-0.0100%, Ni: 0.01-2.99%, N: 0.0001-0.0400%, Ti: 0.001-0.0150%, Al: 0.001-1.000%, and a mixed structure of martensite with a martensite ratio of 80% or more, and carbide content of 90% or less, to enhance thermal conductivity, hardness, and toughness.

Benefits of technology

The steel exhibits thermal conductivity of 25.0 W/m K or more, hardness of 48.0 HRC or higher, and Charpy impact value of 20 J/cm² or more, demonstrating high thermal conductivity, hardness, and toughness, suitable for mold applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a tool steel for hot work, as a metal mold steel having high thermal conductivity, high hardness, high softening resistance, and high toughness, and applicable for die cast and hot stamping.SOLUTION: A tool steel for hot work has a composition comprising, by mass%, over 0.35 to 0.70% C, 0.01-1.20% Si, 0.01-1.50% Mn, 0.30-4.00% Cr, 0.05-3.50% Cu, one kind or two kinds selected from Mo and W comprising 3.00% or less Mo and 6.00% or less W, and 0.50%-3.00% Mo+1 / 2 W, over 0.10 to 0.55% V, and 0.0001-0.0100% B, and has the remainder comprising Fe and inevitable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to hot work tool steel with excellent thermal conductivity. In particular, it relates to mold steel used in high-temperature environments such as die casting and hot stamping. [Background technology]

[0002] In recent years, in the die-casting field, there has been a focus on increasing the strength of aluminum parts for the purpose of reducing the weight of automobiles. The shortening of the processing pitch for parts molding, aimed at improving productivity, has increased the mechanical and thermal load on die-casting molds. As a result, molds are more susceptible to problems such as wear, large cracks, and heat checks. To address these issues, mold materials with excellent hardness and toughness are required. Furthermore, in hot stamping, mold wear caused by scale formation on the surface of the workpiece (steel plate) is a problem, and mold materials require high hardness and resistance to softening.

[0003] Furthermore, die-casting and hot-stamping molds have internal cooling circuits, and the cooling efficiency of the cooling water flowing through these circuits greatly affects the production cycle speed. One way to improve cooling efficiency is to increase the thermal conductivity of the mold. Therefore, in order to meet the aforementioned demand for increased production cycle speed aimed at improving productivity, high thermal conductivity is necessary as a material property.

[0004] Patent documents 1 to 9 propose prior art that attempts to improve the above requirements. First, die-casting mold steels that do not take Cu or B into consideration have been proposed (see, for example, Patent Document 1). However, since the unmentioned Cu and B remain within the range of unavoidable impurities, bainite, an incompletely quenched phase, is easily formed, leading to a problem of insufficient toughness.

[0005] Furthermore, since surface cracking occurs during hot forging, reducing forgeability, hot die steel with a Cu content of 0.02% or less has been proposed (see, for example, Patent Document 2). However, because of the low Cu content, bainite, an incompletely hardened phase, is formed, resulting in a problem of insufficient toughness.

[0006] Furthermore, mold steel containing more than 1.50% Mn has been proposed to ensure hardenability (see, for example, Patent Document 3). However, such excessive addition of Mn leads to a problem of reduced thermal conductivity.

[0007] Furthermore, mold steel containing less than 0.1% of V has been proposed to ensure machinability (see, for example, Patent Document 4). However, such a low amount of V leads to the problem of insufficient hardness after quenching and tempering.

[0008] Furthermore, to suppress the coarsening of γ crystal grains during quenching, molding tools using mold steel containing more than 0.55% V have been proposed (see, for example, Patent Document 5). However, when V is added in such excess, there is a problem of reduced thermal conductivity.

[0009] Furthermore, mold steel containing a high amount of Cr (4.00% or more) has been proposed to ensure corrosion resistance (see, for example, Patent Document 6). However, excessive addition of Cr leads to a problem of reduced thermal conductivity.

[0010] To suppress welding cracks, pre-hardened steel for die-casting molds containing a low amount of carbon (0.35% or less) has been proposed (see, for example, Patent Document 7). However, such a low carbon content leads to the problem of insufficient hardness after quenching and tempering.

[0011] Furthermore, hot work tool steels with a Mo+1 / 2·W content greater than 3.0% have been proposed (see, for example, Patent Document 8). However, there is a problem that the thermal conductivity decreases due to the excessive addition of Mo or W.

[0012] In addition, hot work tool steels containing 3% or more of Ni have been proposed (see, for example, Patent Document 9). The steels described in the claims and examples of this document contain more than 3% of Ni. However, when the content is 3% or more, there is a problem that the thermal conductivity decreases due to the excessive addition of Ni.

Prior Art Documents

Patent Documents

[0013]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

Patent Document 5

Patent Document 6

Patent Document 7

Patent Document 8

Patent Document 9

Summary of the Invention

Problems to be Solved by the Invention

[0014] The problem to be solved by the present invention is to provide a hot work tool steel applicable to die casting, hot stamping, etc., which has high thermal conductivity, high hardness, excellent softening resistance, and high toughness. Hot work tool steel is tool steel used as a tool for machining workpieces in the hot temperature range.

Means for Solving the Problems

[0015] As a result of intensive development by the inventor, by specifying the alloy components within a specific range and further specifying the structure and carbide state of the steel, it has been found that a hot work tool steel having high thermal conductivity, high hardness, excellent softening resistance, and high toughness can be obtained.

[0016] The first means for solving the problem is, in mass%, C: more than 0.35 to 0.70%, Si: 0.01 to 1.20%, Mn: 0.01 to 1.50%, Cr: 0.30 to 4.00%, Cu: 0.05 to 3.50%, One or two of Mo and W, where Mo: 3.00% or less, W: 6.00% or less, and Mo + 1 / 2·W: 0.50% to 3.00%, V: over 0.10 to 0.55%, B: 0.0001 to 0.0100% Characterized by having the above components, with the balance being Fe and inevitable impurities, it is a hot work tool steel.

[0017] Its second means is a hot work tool steel characterized by having, in addition to the chemical components described in the first means, Ni: 0.01 to 2.99% by mass, with the balance being Fe and inevitable impurities.

[0018] Its third means is a hot work tool steel characterized by having, in addition to the chemical components described in either one of the first or second means, N: 0.0001 to 0.0400% by mass, with the balance being Fe and inevitable impurities.

[0019] Its fourth means is a hot work tool steel characterized by having, in addition to the chemical components described in any one of the first to third means, Ti: 0.001 to 0.0150% by mass, with the balance being Fe and inevitable impurities.

[0020] Its fifth means is, in addition to the chemical components described in any one of the first to fourth means, by mass % having Al: 0.001 to 1.000%, with the balance being Fe and inevitable impurities, and it is a hot work tool steel.​​​The sixth method is a hot work tool steel having the chemical composition described in any one of the first to fifth methods, with the remainder being Fe and unavoidable impurities, characterized in that the hot work tool steel has a single-phase martensite structure or a mixed structure of martensite and bainite, wherein the proportion of martensite in the mixed structure is 80% or more.

[0022] The seventh means is a hot work tool steel having the chemical composition described in any one of the first to fifth means, with the remainder being unavoidable impurities, wherein M in the steel 23 M is the percentage of the total carbides in C6 carbides, M6C carbides, M7C3 carbides, M3C carbides, M2C carbides, and MC carbides. 23 This hot work tool steel is characterized by having a ratio of C6 carbide and M6C carbide of 90% or less.

[0023] The eighth means is the hot work tool steel described in the sixth means, further comprising M in the steel 23 M is the percentage of the total carbides in C6 carbides, M6C carbides, M7C3 carbides, M3C carbides, M2C carbides, and MC carbides. 23 This hot work tool steel is characterized by having a ratio of C6 carbide and M6C carbide of 90% or less. [Effects of the Invention]

[0024] Now, the hot work tool steels of each of the above-described means of the present invention, after being quenched and tempered, exhibit high thermal conductivity of 25.0 W / m·K or higher at room temperature, high hardness of 48.0 HRC or higher at room temperature, high softening resistance of 32.0 HRC or higher at room temperature after being held at 600°C for 100 hours after quenching and tempering, and a Charpy impact value of 20 J / cm at room temperature. 2 The above-mentioned high toughness is achieved. Therefore, by using the hot work tool steel of each method of the present invention, it is possible to obtain a material that is suitable for molds, possessing high thermal conductivity, high hardness, high softening resistance, and high toughness.

[0025] Furthermore, in the present invention, High thermal conductivity refers to a thermal conductivity of 25.0 W / m·K or higher at room temperature after quenching and tempering. High hardness means: a hardness of 48.0 HRC or higher at room temperature after quenching and tempering. High toughness means: A Charpy impact value of 20 J / cm² at room temperature after quenching and tempering. 2 That's all. High softening resistance refers to a hardness of 32.0 HRC or higher at room temperature after quenching and tempering, followed by holding at 600°C for 100 hours. [Modes for carrying out the invention]

[0026] First, the reasons for specifying the chemical composition of the hot tool steel used to solve the problems of the present invention, and the reasons for specifying the microstructure and carbide state of this hot tool steel, will be explained below.

[0027] C: More than 0.35 ~ 0.70% Carbon (C) is an element that strengthens the matrix through solid solution and promotes precipitation strengthening by forming carbides. However, if the C content is low, below 0.35%, sufficient quenching and tempering hardness cannot be obtained. On the other hand, if the C content exceeds 0.70%, it promotes segregation and reduces toughness. Therefore, the C content should be between 0.35% and 0.70%, preferably between 0.55% and 0.70%.

[0028] Si: 0.01–1.20% Si is an essential element as a deoxidizing agent during steelmaking. However, if the Si content is less than 0.01%, deoxidation is not sufficient during steelmaking. On the other hand, if the Si content is more than 1.20%, it dissolves in the matrix without forming carbides, reducing the thermal conductivity. Therefore, the Si content should be between 0.01% and 1.20%. However, when the Si content is 0.05% or more, it has the effect of improving hardness by dissolving in the matrix, so preferably, the Si content should be around 0.05%. The percentage must be between % and 1.00%.

[0029] Mn: 0.01–1.50% Mn is an essential element as a deoxidizing agent during steelmaking. However, if the Mn content is less than 0.01%, deoxidation is not sufficient. On the other hand, if the Mn content is more than 1.50%, it dissolves into the matrix and reduces the thermal conductivity. Therefore, the Mn content should be between 0.01% and 1.50%, preferably between 0.05% and less than 0.92%, and more preferably between 0.10% and less than 0.50%.

[0030] Cr: 0.30% to 4.00% Cr is an essential element for improving hardenability and suppressing the reduction in toughness due to bainite formation. However, if the Cr content is less than 0.30%, sufficient toughness cannot be obtained. On the other hand, if the Cr content is more than 4.00%, it dissolves into the matrix and reduces thermal conductivity. Also, if there is too much Cr, the matrix tends to coarseen at high temperatures during tempering. 23 C6 carbides precipitate, reducing softening resistance. Therefore, the Cr content should be between 0.30% and 4.00%, preferably between 0.40% and less than 2.60%, and more preferably between 0.50% and less than 2.10%.

[0031] Cu: 0.05% to 3.50% Cu is an essential element for improving hardenability and suppressing the reduction in toughness due to bainite formation. However, if the amount of Cu is less than 0.05%, sufficient toughness cannot be obtained. On the other hand, if the amount of Cu is more than 3.50%, it will dissolve in the matrix and reduce the thermal conductivity. Therefore, the amount of Cu should be between 0.05% and 3.50%, and preferably between 0.10% and 3.00%.

[0032] It contains one or two of either Mo or W, Mo: 3.00% or less W: 6.00% or less, Mo+1 / 2·W: 0.50-3.00% Mo and W are essential elements for promoting secondary hardening during tempering and increasing quenched-temper hardness. If there is too much Mo or W, the amount of Mo and W remaining in the matrix increases, reducing thermal conductivity. Therefore, Mo + 1 / 2·W should be 3.00% or less, with Mo: 3.00% or less and W: 6.00% or less. On the other hand, if the amount of Mo or W is too low, sufficient hardness after quenching and tempering cannot be obtained. If the amount of Mo+1 / 2·W is too low (less than 0.50%), sufficient hardness after quenching and tempering cannot be obtained. Therefore, the mixture should contain one or two types of Mo and W, with Mo being 3.00% or less, W being 6.00% or less, and Mo+1 / 2·W being 0.50% to 3.00%, preferably Mo+1 / 2·W being 1.50% to 3.00%.

[0033] V: More than 0.10 ~ 0.55% V is an element that promotes secondary hardening during tempering, thereby increasing the hardness after quenching and tempering. However, if V is less than 0.10%, sufficient hardness after quenching and tempering cannot be obtained. On the other hand, if V is more than 0.55%, the amount of V remaining in the matrix increases, reducing the thermal conductivity. Therefore, V should be between 0.10% and 0.55%, and preferably between 0.25% and 0.45%.

[0034] B: 0.0001 to 0.0100% B is an element necessary for improving hardenability and suppressing the reduction in toughness due to bainite formation, even when added in small amounts. However, if the amount of B is less than 0.0001%, sufficient toughness cannot be obtained. This is not possible. On the other hand, if B is too high, coarse carbides are formed during tempering, reducing toughness. Therefore, B should be between 0.0001% and 0.0100%, and preferably between 0.0005% and 0.0075%.

[0035] Ni: 0.01–2.99% Ni is an element that is not necessarily required to be added, but like Cr, it improves hardenability and suppresses the decrease in toughness due to bainite formation. However, if the amount of Ni exceeds 2.99%, it dissolves in the matrix and reduces the thermal conductivity. Therefore, the amount of Ni should be between 0.01% and 2.99%, and preferably between 0.01% and 2.00%.

[0036] N: 0.0001 to 0.0400% While nitrogen (N) is not always necessary to add, it is an effective element for increasing hardness after quenching and tempering, similar to carbon (C). However, adding more than 0.0400% of N increases the smelting time and thus the cost of smelting. Therefore, the amount of N should be between 0.0001% and 0.0400%, and preferably between 0.0001% and 0.0300%.

[0037] Ti:0.150% or less While Ti is not strictly necessary, it is an element that promotes improved hardenability due to B. During quenching, N compoundes with Ti, increasing the amount of solid-solution B and improving hardenability. However, if more than 0.150% Ti is added, coarse TiN is formed, reducing toughness. Therefore, the amount of Ti should be 0.150% or less, and preferably 0.100% or less.

[0038] Al: 0.001–1.000% Al (Al) is not necessarily required, but it is an element that improves hardness by solid-solving in the matrix. However, if the Al content is less than 0.001%, it will not solid-solve in the matrix and improve hardness. On the other hand, if the Al content is greater than 1.000%, it will solid-solve in the matrix and reduce thermal conductivity. Therefore, the Al content should be between 0.001% and 1.000%, and preferably between 0.005% and 0.700%.

[0039] Next, we will describe the microstructure of hot work tool steel. Microstructure in quenching and tempering state: single-phase martensite (martensite ratio (M ratio): 100%), or a mixed structure of martensite and bainite, where the martensite ratio in the mixed structure is 80% or more If a large amount of bainite, which is an incompletely quenched phase, exists in the microstructure in the quenching and tempering state, the toughness will be significantly reduced, and when used as a hot stamping and die-casting mold, sufficient mold life cannot be obtained. Therefore, the microstructure in the quenching and tempering state is either a structure consisting only of single-phase martensite (that is, the martensite ratio M ratio is 100%), or when the microstructure in the quenching and tempering state is a mixed structure of martensite and bainite, the martensite ratio M ratio in the mixed structure is 80% or more.

[0040] Regarding the ratio of specific carbides in hot work tool steel in the quenched and tempered state M in all carbides in the steel 23 Ratio of C6 carbide and M6C carbide: 90% or less In the quenched and tempered state, all carbides in the steel (that is, M 23 C6 carbide, M6C carbide, M7C3 carbide, M3C carbide, M2C carbide, MC carbide) occupied by M 23 The ratio of C6 carbide and M6C carbide is set to 90% or less. This is because M 23 C6 carbide and M6C carbide, which are carbides that tend to coarsen at high temperatures, if more than 90% exist in the steel in the quenched and tempered state, the softening resistance of the steel will decrease.

[0041] Next, the embodiments of the present invention will be sequentially described with reference to the table as appropriate.

[0042] As examples of the present invention, Table 1 and Table 2 below show the chemical compositions of Invention Steels No. 1 to No. 78. Table 3 shows the chemical compositions of Comparative Steels No. 79 to No. 97. The balance is Fe and inevitable impurities. The inventive steels and comparative steels of these chemical compositions, No. 1 to 83, were each melted in a vacuum induction melting furnace, and the resulting 100 kg steel ingots of each No. were hot-forged into blocks 65 mm wide and 30 mm high. Next, after annealing each of these forged materials at 870°C, round bars with a diameter of 20 mm and a length of 160 mm were taken from the midpoint between the surface and the center. Furthermore, each of these round bars was heated to 1030°C to ensure uniformity, then quenched by air cooling, followed by two tempering cycles at 570-670°C. After that, the microstructure and precipitated carbides of each steel material in the quenched and tempered state were observed, and various properties shown in Tables 4 to 6 were investigated.

[0043] The various properties mentioned above include thermal conductivity (W / m·K), hardness after quenching and tempering (HRC), and Charpy impact value (J / cm²) which indicates toughness. 2 ) and hardness after high-temperature holding (HRC), i.e., resistance to softening.

[0044] [Table 1]

[0045] [Table 2]

[0046] [Table 3]

[0047] 1) For microstructural observation, each sample in the quenched and tempered state was polished to a mirror finish on a surface parallel to the forging direction, then etched with Nital, and observed using a scanning electron microscope (SEM). Total area: 50,000 μm² 2 In the region, the presence or absence of bainite was checked, and if bainite was found, the area ratio was calculated as a percentage using image analysis.

[0048] 2) For carbide observation, test specimens were prepared by polishing the surface parallel to the forging direction of each sample after quenching and tempering, and then using the extraction replica method. These test specimens were then examined using bright-field imaging with a transmission electron microscope, covering a total area of ​​500 μm².2 Observations were made in the region. The carbide species were determined from the results of electron diffraction and the shape of the carbides. The captured photographs were analyzed to determine the proportion of M in the total carbides. 23 The total area ratio of C6 carbides and M6C carbides was calculated as a percentage.

[0049] 3) The thermal conductivity was measured using the laser flash method. Each sample, after quenching and tempering, was finished into a cylindrical shape with a diameter of 10 mm × 1 mm and subjected to testing. The thermal conductivity was measured at room temperature.

[0050] 4) The hardness after quenching and tempering was measured at room temperature using a Rockwell hardness tester. For each quenched and tempered sample, the hardness of the surface perpendicular to the forging direction was measured.

[0051] 5) Toughness was evaluated by a Charpy impact test at room temperature. The test specimens were quenched and tempered. The specimens were prepared from steel samples after the initial processing. The specimen shape was a 2mm U-notched Charpy test specimen, with the notch direction perpendicular to the forging direction.

[0052] 6) Softening resistance was evaluated by holding steel samples after quenching and tempering at 600°C for 100 hours, air-cooling them, and then measuring their hardness at room temperature using a Rockwell hardness tester.

[0053] The structure of 1) and the state of the carbides of 2) are shown in Tables 1 to 3 above. The M ratio in the structure in the table is the percentage of martensite area in the structure. Also, the M6C carbides and M in the total carbides are shown. 23 The total area percentage of C6 carbides is shown as a percentage.

[0054] Tables 4 and 5 below show the thermal conductivity measured in 3) above, the hardness after quenching and tempering measured in 4), the Charpy impact value (toughness) measured in 5), and the hardness after high-temperature holding (softening resistance) measured in 6), for the inventive steel, and further, Table 6 below shows the comparative steel.

[0055] [Table 4]

[0056] [Table 5]

[0057] [Table 6]

[0058] The steel of the present invention has the chemical composition of No. 1 to 78 in Tables 1 and 2, with a martensite area ratio of 80% or more, and M6C carbide and M in the total carbides. 23 The total area ratio of C6 carbides is kept below 90%. These inventive steels, as shown in Tables 4 and 5, Nos. 1 to 78, have a thermal conductivity of 25.0 W / m·K or higher, a hardened hardness of 48.0 HRC or higher, and a Charpy impact value of 20 J / cm². 2 As described above, the hardness after high-temperature holding was 32.0 HRC or higher. Thus, by focusing on the component composition, microstructure, and carbides, the hot work tool steel of this application, when quenched and tempered, possesses high thermal conductivity, high hardness, high softening resistance, and high toughness, making it suitable for use in molds and the like.

[0059] In contrast, in the comparative steel, the chemical composition of each No. 79 to 97 in Table 3 falls outside the range of components specified in this application. Furthermore, the microstructure is a mixed structure of martensite and bainite with a low area ratio of martensite, and M6C carbide and M 23 Some samples contain an excessively high proportion of C6 carbides by total surface area. Furthermore, as shown in Table 6, Nos. 79 to 97, the properties of these comparative steels were inferior to those of the hot work tool steel of the present invention in one or more of the following characteristics: thermal conductivity, hardness, softening resistance, or toughness.

[0060] The comparative examples are described in more detail below. In No. 79, as shown in Table 3, the carbon content is 0.33%, which is lower than the specified value, and as shown in Table 6, the hardened and tempered hardness is 46.4 HRC, which is lower than the specified value. In No. 80, as shown in Table 3, C was 0.73%, which is higher than the specified value, and as shown in Table 6, the Charpy impact value was 14.2 J / cm². 2 It is below the regulation level. In No. 81, as shown in Table 3, the Si content is 1.27%, which is more than specified, as shown in Table 6. The sea urchin's thermal conductivity is 23.5 W / m·K, which is lower than specified. In sample No. 82, as shown in Table 3, the Mo content is 1.54%, which is higher than specified, and as shown in Table 6, the thermal conductivity is 23.8 W / m·K, which is lower than specified. In No. 83, as shown in Table 3, the Cr content was 0.23%, which is lower than the specified amount, and the M ratio, which is the proportion of martensite, was also low at 74%. As shown in Table 6, the Charpy impact value was 15.5 J / cm². 2 It is below the regulation level. In No. 84, as shown in Table 3, Cr was 4.12%, which is higher than the specified amount, and furthermore, M6C carbide and M in the total metal carbides. 23 The total area ratio of C6 carbides is slightly high at 91%, and as shown in Table 6, the thermal conductivity is 22.9 W / m·K, which is lower than specified, and the hardness after high-temperature holding is 31.6 HRC, which is also lower than specified. In No. 85, as shown in Table 3, the Ni content is 3.12%, which is higher than specified, and as shown in Table 6, the thermal conductivity is 23.1 W / m·K, which is lower than specified. In No. 86, as shown in Table 3, the Cu content was 0.03%, which is less than the specified amount, and the M ratio, which is the proportion of martensite, was also slightly low at 78%. As shown in Table 6, the Charpy impact value was 15.4 J / cm². 2 It is below the regulation level. In No. 87, the Cu content is 3.62%, which is slightly higher than specified, and as shown in Table 6, in No. 75, the thermal conductivity is 22.7 W / m·K, which is lower than specified. In sample No. 88, as shown in Table 3, the Mo content is 3.12%, which is less than specified, and the Mo+1 / 2·W content is 3.12%, which is more than specified. As shown in Table 6, the thermal conductivity is 22.8 W / m·K, which is lower than specified. In No. 89, as shown in Table 3, W is 6.47%, which is higher than specified, and Mo+1 / 2·W is 3.24%, which is also higher than specified. As shown in Table 6, the thermal conductivity is 24.2 W / m·K, which is lower than specified. In No. 90, as shown in Table 3, the Mo+1 / 2·W content is 3.46%, which is higher than specified, and as shown in Table 6, the thermal conductivity is 24.2 W / m·K, which is lower than specified. In No. 91, as shown in Table 3, the Mo+1 / 2·W content was 0.41%, which is less than the specified value, and as shown in Table 6, the quenched and tempered hardness was 46.6 HRC, which is lower than the specified value. In No. 92, as shown in Table 3, V is 0.08%, which is less than the specified value, and as shown in Table 6, the hardness after quenching and tempering is 42.3 HRC, which is lower than the specified value. In No. 93, as shown in Table 3, V is 0.61%, which is higher than specified, and as shown in Table 6, the thermal conductivity is 24.2 W / m·K, which is lower than specified. In No. 94, as shown in Table 3, V is 0.61%, which is higher than specified, and as shown in Table 6, the thermal conductivity is 24.2 W / m·K, which is lower than specified. In No. 95, as shown in Table 3, B was 0.012%, which is higher than the specified value, and as shown in Table 6, the Charpy impact value was 17.2 J / cm². 2 It is below the regulation level. In No. 96, as shown in Table 3, the Ti content was 0.162%, which is higher than specified, and as shown in Table 6, the Charpy impact value was 16.0 J / cm². 2 It is below the regulation level. In No. 97, as shown in Table 3, the Al content is 1.210%, which is higher than specified, and as shown in Table 6, the thermal conductivity is 22.5 W / m·K, which is lower than specified.

Claims

1. In mass%, C: more than 0.35 to 0.70%, Si: 0.01 to 1.20%, Mn: 0.01-1.50%, Cr:0.30〜4.00%、 Cu: 0.05-3.50%, one or two of Mo and W, wherein Mo: 3.00% or less, W: 6.00% or less, and Mo+1 / 2 W: 0.50% to 3.00%; V: more than 0.10 ~ 0.55%, B:0.0001〜0.0100%、 and the balance consisting of Fe and unavoidable impurities.

2. 10. A hot work tool steel comprising, in addition to the chemical components set forth in claim 1, 0.01 to 2.99% by mass of Ni, the balance being Fe and unavoidable impurities.

3. 3. A hot work tool steel comprising, in addition to the chemical components set forth in claim 1 or 2, 0.0001 to 0.0400% by mass of N, the balance being Fe and unavoidable impurities.

4. 4. A hot work tool steel comprising, in addition to the chemical components set forth in claim 1, 0.001 to 0.0150% by mass of Ti, and the balance being Fe and unavoidable impurities.

5. 5. A hot work tool steel comprising, in addition to the chemical components set forth in any one of claims 1 to 4, Al: 0.001 to 1.000%, by mass%, with the balance consisting of Fe and unavoidable impurities.

6. 10. A hot work tool steel having the chemical composition set forth in any one of claims 1 to 5, with the balance being Fe and unavoidable impurities, characterized in that the hot work tool steel has a martensite single phase structure or a mixed structure of martensite and bainite, with the proportion of martensite in the mixed structure being 80% or more.

7. A hot work tool steel having the chemical composition according to any one of claims 1 to 5, with the balance consisting of unavoidable impurities, wherein M in the steel 23 The percentage of M in the total carbides of C6 carbide, M6C carbide, M7C3 carbide, M3C carbide, M2C carbide and MC carbide is 23 A hot work tool steel characterized in that the proportion of C6 carbides and M6C carbides is 90% or less.

8. The hot work tool steel according to claim 6, further comprising M in the steel. 23 The percentage of M in the total carbides of C6 carbide, M6C carbide, M7C3 carbide, M3C carbide, M2C carbide and MC carbide is 23 A hot work tool steel characterized in that the proportion of C6 carbides and M6C carbides is 90% or less.